2015
DOI: 10.1101/cshperspect.a021717
|View full text |Cite
|
Sign up to set email alerts
|

The Origins and Organization of Vertebrate Pavlovian Conditioning

Abstract: Pavlovian conditioning is the process by which we learn relationships between stimuli and thus constitutes a basic building block for how the brain constructs representations of the world. We first review the major concepts of Pavlovian conditioning and point out many of the pervasive misunderstandings about just what conditioning is. This brings us to a modern redefinition of conditioning as the process whereby experience with a conditional relationship between stimuli bestows these stimuli with the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 226 publications
(234 reference statements)
1
92
0
Order By: Relevance
“…During appetitive Pavlovian conditioning, a mental association is formed between reward-predictive stimulus and the unconditioned appetitive event (e.g., food item) with which it is associated (Fanselow & Wassum 2015, Berridge 2001, Rescorla & Solomon 1967, Dickinson & Balleine 2002). Subsequently, by recalling the more general (i.e., specific identity-independent) motivational features of the paired reward (e.g., nutritive or fluidic properties, not specific taste), a reward cue can motivate a broad range of instrumental actions (though typically those earning a categorically similar reward) (Corbit & Balleine 2005, Balleine 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During appetitive Pavlovian conditioning, a mental association is formed between reward-predictive stimulus and the unconditioned appetitive event (e.g., food item) with which it is associated (Fanselow & Wassum 2015, Berridge 2001, Rescorla & Solomon 1967, Dickinson & Balleine 2002). Subsequently, by recalling the more general (i.e., specific identity-independent) motivational features of the paired reward (e.g., nutritive or fluidic properties, not specific taste), a reward cue can motivate a broad range of instrumental actions (though typically those earning a categorically similar reward) (Corbit & Balleine 2005, Balleine 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The invigoration of instrumental activity induced by the sucrose-predictive cue could be interpreted to reflect primarily the general (rather than specific) form PIT, because the stimulus invigorated responding on an action that, in training, earned a distinct, grape-flavored polycose reward (Dickinson & Balleine 2002, Cartoni et al 2013, Fanselow & Wassum 2015, Balleine 1994, Dickinson & Balleine 1994). Indeed, sucrose and polycose work through separate taste channels in the rat (Sclafani 1991, Ackroff et al 1993) and were confirmed here to be discriminable.…”
Section: Discussionmentioning
confidence: 99%
“…The approach was used in several recent publications to test the psychological relevance of distributed neural ensembles activated during learning in a contextual fear-conditioning task (see Fanselow and Wassum 2015). In contextual fear conditioning, animals receive footshocks in a particular context (the conditioning box) that contains multimodal sensory cues (generally distinct visual, tactile, and odor cues).…”
Section: Optogenetic Manipulation During Retrievalmentioning
confidence: 99%
“…Instead of being exact "copies" of unconditioned responses (URs), CRs may be substantially different from URs, providing the organism with preparatory or compensatory mechanisms in advance of reward or punishment. For example, while a single electric shock increases behavioral activity, during fear conditioning repeated pairings of shocks with a CS result in the development of freezing responses to the cue (Fanselow and Wassum 2015). Thus, as stated by Boakes (1977): "we need not only to understand how the animal learns to associate the two events but also what the behavioral consequences of such learning are.…”
mentioning
confidence: 99%